International Tourist Arrivals Volatility Comovements and Spillovers. The Case of Thailand - BUNNAG, Tanattrin (Journal of Environmental Management and Tourism; Vol 6 No 1 (2015): JEMT Volume VI Issue 1(11) Summer 2015, 2016)
This paper examined the international tourist arrivals volatility comovements and spillovers for Malaysian (GML), Japanese (GJP), British (GUK) and American (GUS) tourists. The data used in this study was the monthly data from 1985 to 2015. The three Multivariate GARCH models, namely the VAR (5)-diagonal VECH and the VAR (5)-diagonal BEKK, were employed. The empirical results overall showed that the estimates of the VAR (5)-diagonal VECH parameters are statistically significant in the case of GML with GUS and GJP with GUS except in the case of GML with GJP, GML with GUK, GJP with GUK and GUK with GUS. This indicates that the short run persistence of shocks on the dynamic conditional correlations is greatest for GML with GJP, while the largest long run persistence of shocks to the conditional correlations for GML with GUS. In addition, the estimates of the VAR (5)-diagonal BEKK parameters are statistically in the case of GML with GUK, GML with GUS and GUK with GUS except in the case of GML with GJP, GJP with GUK and GJP with GUS. This indicates that the short run persistence of shocks on the dynamic conditional correlations is greatest for GJP with GUK, while the largest long run persistence of shocks to the conditional correlations for GML with GUK. Finally, we found that the best model in volatility analysis is the VAR (5) - diagonal BEKK model. Therefore, we can say Japanese tourists with British tourists are the most susceptible for the short run. But for the long run, Malaysian tourists with British tourists are the most susceptible.
Keywords: the international tourist arrivals volatility; comovements and spillovers; multivariate GARCH models